Percepción del cuidado humanizado de enfermería y la satisfacción del familiar de usuarios Hospital Victor Lazarte Echegaray Trujillo - Rodríguez Alfaro, Carmen Gladys (2019)
This present research work, descriptive correlational type, whose objective was to determine the relationship between the perception of humanized nursing care and the level of satisfaction of the of the relative of the user of the Emergency Service Víctor Lazarte Echegaray Hospital. The sample consisted of 80 users and relatives of the emergency service. For the collection of data, two questionnaire instruments on Perception of Humanized Nursing Care and User Satisfaction Questionnaire, previously validated, were used, reaching the following conclusions: 57.5% obtained a good perception about the humanized care of Nursing and the 42.5% poor perception, in terms of the level of satisfaction of the family member, 53.75% said they were satisfied with the care provided by the nurse and 46.25% said they were dissatisfied. There is a relationship between the humanized nursing care and the level of satisfaction of the user's family member. p <0.004